(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
Synonymy is one of the central phenomena studied in lexical semantics because it reveals the complexity and richness of word meaning in language. This article examines the concept of synonymy, its major types, characteristics, and functions in communication. Special attention is paid to the semantic relationships between synonymous words and their role in organizing lexical systems. The study discusses absolute, ideographic, stylistic, and contextual synonyms, emphasizing that complete synonymy is extremely rare in natural languages. The article also explores the significance of synonymy in vocabulary enrichment, stylistic expression, translation, lexicography, and language teaching. Through the analysis of semantic similarity, emotional coloring, and contextual usage, the paper demonstrates that synonymy is an essential component of lexical semantics and an important mechanism of effective communication